Analysis of insect cuticular hydrocarbons using matrix-assisted laser desorption/ionization mass spectrometry - Cvacka, Josef; Jiros, Pavel; Sobotník, Jan; Hanus, Robert; Svatos, Ales (Journal of chemical ecology, 2006)
Insect cuticular hydrocarbons (CHCs) were probed by matrix-assisted laser desorption/ionization (MALDI) time-of-flight (TOF) mass spectrometry with a lithium 2,5-dihydroxybenzoate matrix. CHC profiles were obtained for 12 species of diverse insect taxa (termites, ants, a cockroach, and a flesh fly). MALDI spectra revealed the presence of high molecular weight CHCs on the insect cuticle. Hydrocarbons with more than 70 carbon atoms, both saturated and unsaturated, were detected. When compared with gas chromatography/mass spectrometry (GC/MS), MALDI-TOF covered a wider range of CHCs and enabled CHCs of considerably higher molecular weight to be detected. Good congruity between GC/MS and MALDI-TOF was observed in the overlapping region of molecular weights. Moreover, a number of previously undiscovered hydrocarbons were detected in the high mass range beyond the analytical capabilities of current GC/MS instruments. MALDI was shown to hold potential to become an alternative analytical method for insect CHC analyses. The ability of MALDI to discriminate among species varying in the degree of their relatedness was found to be similar to GC/MS. However, neither MALDI-MS nor GC/MS data were able to describe the phylogenetic relationships.
Keywords: spektrometrie hmotnostní - ionizace laserem za účasti matrice; Insecta; chloroform; Animals; Hydrocarbons; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; hmyz; uhlovodíky; Chloroform; zvířata